Literature Study: The Effect of the Working Environment on Employee Performance - Aditya Angga Kusuma (Business and Entrepreneurial Review, 2021)
The work environment is one of the factors that can affect employee performance. A harmonious relationship between employees and superiors, colleagues, and subordinates can have a positive impact on these employees. This also affects the performance which tends to be good. This study aims to measure how the work environment affects employee performance. The method used in this research is qualitative with data collection techniques through literature studies where the data used is secondary data which is the result of research from previous researchers. The references used in this study are 10 scientific papers which will be reviewed again to provide an overview of the effect of the workplace on employee performance. Based on a literature study that has been conducted, it shows that the work environment, both physical and non-physical, has a partial and also simultaneous influence on employee performance.